PENGARUH PENGGUNAAN TEKNOLOGI INTERAKTIF BERBASIS PHET TERHADAP HASIL BELAJAR MATERI OPERASI HITUNG MATEMATIKA SISWA KELAS II UPT SPF SD INPRES MALENGKERI 1: Penelitian Eksperimen - Asni, Nur; Andi Husniati; Andi Ardhilla Wahyudi (STKIP Subang, 2026)
This study aims to determine whether there is an effect of using PhET-based interactive technology on students' learning outcomes in mathematics operations. This study is quantitative in nature, using a One Group Pretest-Posttest Design. The population of this study was all fourth-grade students. Saturated sampling was used, with a total of 21 students consisting of 11 boys and 10 girls. The data collection instruments used were student activity observation sheets and tests to measure students' learning outcomes in mathematical operations. The data analysis techniques used were descriptive and inferential analysis, namely the t-test. The descriptive statistical data results show that the average score for learning outcomes in mathematical calculation before using PhET-based interactive technology was 53.80, while the average score for learning outcomes after using PhET-based interactive technology was 87.14. This shows that there is a difference in learning outcomes in mathematical calculation before and after using PhET-based interactive technology. The t-test analysis data shows that the t-count = 2.429 and t-table = 1.725, so t-count = 2.429 > t-table 1.725, which means H0 is rejected and H1 is accepted. Therefore, it can be concluded that the use of PhET-based interactive technology has an effect on the mathematical calculation operations of second-grade students at UPT SPF SD Inpres Malengkeri 1.